2009
DOI: 10.1016/j.jvs.2008.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 1-year mortality after elective abdominal aortic aneurysm repair

Abstract: Predictors of 1-year mortality can identify patients less likely to benefit from elective AAA repair. These factors differ for open repair vs EVAR and should be considered in individual patient decision-making. Our EVAR model had less impact on 1-year survival, even if CHF and large AAA diameter were present. However, a combination of age, COPD, renal insufficiency, and need for suprarenal clamping have significant impact on 1-year mortality after open AAA repair. Consideration of these variables should assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
85
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 32 publications
11
85
1
6
Order By: Relevance
“…These data were consistent with a recently published study that showed no influence on 1-year mortality after endovascular repair [37]. Our EVAR group follow-up continued for 4 years and then was mathematically extrapolated.…”
Section: Discussionsupporting
confidence: 92%
“…These data were consistent with a recently published study that showed no influence on 1-year mortality after endovascular repair [37]. Our EVAR group follow-up continued for 4 years and then was mathematically extrapolated.…”
Section: Discussionsupporting
confidence: 92%
“…Together, the CG mortality was significantly lower than the 20% mortality caused by open surgical repair, of which patients with symptomatic and/or ruptured were excluded for the analysis. 15,32,33 In this study, the final occurrences of type I and type II endoleaks were 11.8% and 8.1%, respectively. The results were consisted with the findings of meta-analysis that the event-occurring rate of endoleaks during follow-up was 18% (95% confidence intervals, 14e23%).…”
Section: Discussionmentioning
confidence: 50%
“…10) Less invasive treatments, such as Ch-EVAR might therefore be more appropriate than open surgery. The therapeutic efficacy and safety of endovascular treatments for JAAs have been reported.…”
Section: Discussionmentioning
confidence: 99%